2016
DOI: 10.1021/acs.est.6b03393
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Organoclay/Micelle Action for the Adsorption of Diclofenac

Abstract: A Na-smectite clay mineral (Na-Mt) was exchanged with various amounts of benzyldimethyltetradecyl ammonium chloride cationic surfactant (BDTAC) up to four times the cation exchange capacity (CEC). The adsorption properties of these organoclays as well as a coupled micelle/organoclay process were evaluated to remove an anionic pharmaceutical product, the diclofenac (DCF), recognized as a recalcitrant compound for conventional water treatments and to be poorly adsorbed onto untreated clay mineral. The DCF affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
4
29
0
1
Order By: Relevance
“…With the observation of additional bands related to those of the pharmaceuticals, FTIR technique confirms proper the adsorption of NFX onto layered materials onto layered materials (Figure 4). Additionally, this technique can give new insights in the moieties of the molecules in interaction with the layered materials as it could be discussed in previous research works (Guégan et al 2015, De Oliveira and Guégan 2016, De Oliveira et al 2017).…”
Section: Adsorption Of Zwitterionic Species: Case Of the Amoxicillin mentioning
confidence: 93%
See 3 more Smart Citations
“…With the observation of additional bands related to those of the pharmaceuticals, FTIR technique confirms proper the adsorption of NFX onto layered materials onto layered materials (Figure 4). Additionally, this technique can give new insights in the moieties of the molecules in interaction with the layered materials as it could be discussed in previous research works (Guégan et al 2015, De Oliveira and Guégan 2016, De Oliveira et al 2017).…”
Section: Adsorption Of Zwitterionic Species: Case Of the Amoxicillin mentioning
confidence: 93%
“…As expected, the proper intercalation of the surfactants within the interlayer space of the starting Na Since the adsorption properties of the organoclays mainly depend on the kind of surfactants used, two different surfactants of different nature (nonionic and cationic) and saturated and unsaturated were used. Thus, the prepared materials display complementary properties: from cation exchange capacity, and hydrophilicity for untreated Na-Mt, dual hydrophilicity/phobicity for Brij 0.4 -Mt; to hydrophobicity or organophilicity and even possible anion adsorption ability for BDTA-Mt (Guégan et al 2015, De Oliveira and Guégan 2016, De Oliveira et al 2017, De Oliveira et al 2018. In addition, the difference…”
Section: Organoclay Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Materials such as zeolite [10], clay minerals [11,12] and other organo-derived clay materials [13,14,15] have been reported to be promising candidates in the treatment of wastewater due to their excellent surface characteristics. Recent studies have reported that phosphate minerals represent promising materials in the treatment of wastewaters for the removal of fluoride and heavy metals [16,17].…”
Section: Introductionmentioning
confidence: 99%